Application of Numbered Heads Together Learning Model in an Effort to Improve Skills of Writing Argumentation Paragraphs - Zai, Juwita Suriani; Kartolo, Rahmat (International Journal of Educational Research Excellence (IJERE), 2025)
This study aims to improve the argumentative writing skills of Class X students at SMK Negeri 1 Lolofitu Moi through the application of the Numbered Heads Together (NHT) model. This model was chosen to help students overcome difficulties in writing arguments. The research was conducted using Classroom Action Research (PTK) with 21 students as subjects. Data collection techniques included observation, field notes, interviews, questionnaires, documentation, and argumentative writing tests. Data were analyzed qualitatively and quantitatively, with validity ensured through peer discussions and triangulation. The study's success was measured by improvements in both learning processes and outcomes. The results show that the NHT model received positive responses from students, increasing their engagement and enthusiasm for learning. The average argumentative writing score improved significantly from 57.33 in the pre-action stage to 70.61 at the end of cycle I, and further to 77.04 at the end of cycle II, marking a 32.26% increase. Improvements were observed across various writing aspects: content (13.33%), organization (7.22%), vocabulary (26.94%), language use (17.54%), and mechanics (10.80%). These findings confirm that the NHT model effectively enhances students' argumentative writing skills.